Research on Vocational Education in Indonesia: A Bibliometric Analysis - Ronal Watrianthos; Ambiyar Ambiyar; Fahmi Rizal; Nizwardi Jalinus; Waskito Waskito (JTEV (Jurnal Teknik Elektro dan Vokasional), 2022)
Indonesia's education system separates vocational education from academic education. Vocational education, which was previously not a key focus for prospective students, should now be on par with academic education at both the secondary and higher education levels. However, research on Vocational Education in Indonesia is still limited, particularly articles in reliable indexed databases; therefore, research on Vocational Education in Indonesia is still readily available. This research aims to map studies in bibliometrics connected to research trends in Vocational Education in Indonesia. This study does a statistical analysis of the number of publications on "Pendidikan Vokasi" in Bahasa during the previous five years. The Dimensions database is used for the study dataset, which is processed using Bibliometrix utilizing R-Tool and displayed with Vosviewer. The bibliometric study of the "Pendidikan Vokasi" research resulted in 2500 articles crawling in journals or proceedings on the Dimensions database. A. Ambiyar, N. Jalinus, and N. Erizon. Three names are incredibly fruitful in terms of creating research in this sector. At the same time, Padang State University has the most links to the issue. According to the findings of the bibliometric investigation, the Jurnal Pendidikan Vokasi is the leading generator of publications on the topic. Bibliometric mapping of the study subject "Pendidikan Vokasi" using the VOSviewer, on the other hand, discovered that trend research exclusively mentioned schools (SMK) and learning techniques or models. During this period, there was little research on the industry.